Floral polymorphism in Polygonum bistorta L. (Bangladesh Journal of Plant Taxonomy, 2018)
In the present study, new type of floral polymorphism (tristylous-like flowers) in Polygonum bistorta L., i.e., L-, M-, and S-styles (long, medium and short, respectively) is reported. This tristylous was not only present in different populations but also in a single inflorescence. Although the heights of styles and anthers in the three morphs of flowers differed, their ancillary tepal size, pollen polymorphism, and stigma polymorphism were found similar. The ratio of M-flowers was far lower than those of L- and S-flowers. Unlike the solid nectar of other Polygonum species, fluid nectar was present in Polygonum bistorta, which reflects its specialized state. Different from most of other hetereostylous species with tubular flowers and Polygonum jucundum with open distylous flowers, Polygonum bistorta contains semi-open flowers. Our findings suggest that P. bistorta represents special floral polymorphism in Polygonum and is an ideal plant species for studying the evolution of floral breeding system in Polygonum.Bangladesh J. Plant Taxon. 25(1): 1-11, 2018 (June)